2010
DOI: 10.19030/jabr.v26i4.309
|View full text |Cite
|
Sign up to set email alerts
|

A New Look At Management Accounting

Abstract: <h2 style="page-break-after: auto; text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none;"><span style="font-family: Times New Roman;"><span style="color: black; font-size: 10pt; font-weight: normal; mso-themecolor: text1;">This paper presents a comparison of the traditional management accounting with the new approach of management accounting with the use of latest information technology and manufacturing technologies.<span style="mso-spacerun: yes;">&nbsp; </span>T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A budgeted rate and usage should be used at the beginning of the period in order for the profit centers to budget their overhead rate into their product or service. The implementation of this proposed approach and procedure is needed to allow business firms to better understand resource consumption and profitability of the product and services they provide their clientele (for further discussion on this topic, see (for example) Talha et al , 2010; Federowicz et al , 2010; Huang and Fang, 2008; Capps and Timlin, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A budgeted rate and usage should be used at the beginning of the period in order for the profit centers to budget their overhead rate into their product or service. The implementation of this proposed approach and procedure is needed to allow business firms to better understand resource consumption and profitability of the product and services they provide their clientele (for further discussion on this topic, see (for example) Talha et al , 2010; Federowicz et al , 2010; Huang and Fang, 2008; Capps and Timlin, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The warranty administrator should hold a review session with the responsible parties for discovered inefficiencies. For maximized effectiveness, top management involvement is essential (for additional information on activity based costs (ABC), see for example Vaughn et al , 2010; Talha et al , 2010; Federowicz et al , 2010; Huang and Fang, 2008).…”
Section: Research Objectives and Propositionsmentioning
confidence: 99%
“…Cost management accounting application is the use of internal accounting data in the information system of enterprise at a variety of levels and scopes to make plans, analyze cost fluctuations, thereby helping managers make decisions (Godil & Shabib-ul-Hasan, 2018). Talha, Raja, and Seetharaman (2010) supposed cost management accounting application is the integration of the accounting process into control and evaluation of business operations of an enterprise to improve its performance. Cost management accounting information application provides managers with a basis for making decisions instead of depending on conjecture and experience (Hansen & Mowen, 2006).…”
Section: Cost Management Accounting Applicationmentioning
confidence: 99%
“…In the past decades, cost management accounting has developed strongly and plays an important role in enterprise administration to help managers have a basis for decision-making. The study of Talha et al (2010) showed the positive contribution of the cost management accounting systems in the computer environment with the application of ERP systems to increasingly promote support roles for managers in business process management. The typical studies that can be stated including the study of Pomberg, Pourjalali, Daniel, and Kimbro (2012) about the management accounting information system in Vietnam.…”
Section: International Researchmentioning
confidence: 99%
“…Talha et al (2010) suggested an innovative method of management accounting by integrating BSC, total quality management (TQM) and activity-based costing (ABC). Chavan (2009) and also used BSC to create BSC performance system.…”
Section: Balanced Scorecardmentioning
confidence: 99%